2016
DOI: 10.1097/sap.0000000000000385
|View full text |Cite
|
Sign up to set email alerts
|

Primary On-top Plasty for Treatment of Short-type Postaxial Polydactyly of the Foot

Abstract: This on-top procedure is useful for improving toe lengthening and bone alignment correction with minimal functional disturbance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Takagi et al (2015) performed an on-top plasty for a floating finger to achieve cosmesis with the preservation of five digits. Usami et al (2016) described their primary operation with on-top plasty for lengthening of short-type postaxial polydactyly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Takagi et al (2015) performed an on-top plasty for a floating finger to achieve cosmesis with the preservation of five digits. Usami et al (2016) described their primary operation with on-top plasty for lengthening of short-type postaxial polydactyly.…”
Section: Discussionmentioning
confidence: 99%
“…On-top plasty has traditionally been recommended using a circumferential incision and mobilizing the ulnar duplicate on its neurovascular pedicle and dorsal veins to replace the distal radial duplicate. However, postoperative complications are relatively common, including swelling, a shortened new thumb, narrow first web and unpleasant dorsal scar formation (Al-Qattan and Al-Qattan, 2017; Nakarmi, 2019; Usami et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are rare forms of polydactyly that require more complex surgical procedures to achieve satisfactory correction. For example, Satosh et al ( 3 ) reported a case of polydactyly with short toe deformity that was successfully treated with an “on-top plasty” technique involving osteotomy and transfer at the phalangeal level. They were able to improve the length of the toe with this technique.…”
Section: Introductionmentioning
confidence: 99%
“…Polydactyly of the foot is among the most common congenital anomalies of the foot. It is characterized by six toes, with or without duplication of the corresponding metatarsals or phalanges [1]. The manifestations of polydactyly of the foot may range from vestigial soft-tissue masses to an additional fully formed digit.…”
Section: Introductionmentioning
confidence: 99%
“…in polydactyly surgery because these aspects have a significant effect on the postoperative results and appearance [7,15,16]. Usami et al [1] described four cases of on-top plasty to lengthen the toe in short-type postaxial polydactyly of the foot. The procedure involved separating and elevating the fifth toe with the neurovascular bundle in the metatarsophalangeal joint (distal component), followed by transferring the elevated toe ray to the top of the remaining proximal phalanx (proximal component) of the neighboring sixth toe after osteotomy.…”
mentioning
confidence: 99%